Leadership enhancing the lessons of experience - Hughes, Richard L.; Ginnett, Robert C.; Curphy, Gordon J. (McGraw Hill Education, 2022)
"The book's overall structure remains essentially the same, following our conceptualization of leadership as a process involving an interaction among leaders, followers, and situations. So once again Part One of our text looks at the nature of the leadership process itself as well as how a person becomes a better leader. Part Two is titled Focus on the Leader, with Parts Three and Four logically following as Focus on the Followers and Focus on the Situation. And also continuing the format of previous editions, there is a specific "skills chapter" in each of those parts addressing essential leadership competencies appropriate to each of those four broad areas"-- Provided by publisher